Direct Observation of Molecular Orbital Mixing in a Solvated Organometallic Complex1. Issue 37 (23rd July 2013) - Suljoti, Edlira; Garcia‐Diez, Raul; Bokarev, Sergey I.; Lange, Kathrin M.; Schoch , Roland; Dierker, Brian; Dantz, Marcus; Yamamoto, Kenji; Engel, Nicholas; Atak, Kaan; Kühn, Oliver; Bauer, Matthias; et al.
<x xml:space="preserve">Abstract</x> Fundamental processes: Charge donation/backdonation in the [Fe(CO)5] molecule in solution was measured by resonant inelastic X‐ray scattering. This method can be used to selectively probe the electronic structure at each atom in the iron–carbonyl bond.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>